Students’ Scientific Literacy Skills: A Preliminary Study for Developing a Deep Learning–Based E-Module - Yulista Dewi Fajar Sari; Insih Wilujeng; Susilowati Susilowati (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2026)
This study aims to analyze eighth-grade students' scientific literacy skills as a foundational assessment for developing a Deep Learning-based E-Module on the topic of Matter and Its Changes. Employing a quantitative descriptive approach with mixed-methods supplementation, the research involved 32 students at Bojonegoro Integrated Model Junior High School selected through random sampling. Data were collected using a scientific literacy test aligned with OECD (2025) PISA framework—measuring three core competencies: explaining scientific phenomena, evaluating and designing scientific investigations, and interpreting data and scientific evidence—complemented by classroom observations and stakeholder interviews. Quantitative data were analyzed using percentage achievement formulas and categorized according to established criteria, while qualitative data underwent thematic analysis. Results indicate that students' scientific literacy falls within the medium category (48.27% average), with explaining phenomena scoring highest (51.37%) and investigation design lowest (46.58%). Classroom observations revealed 58.3% teacher-centered instruction with minimal inquiry opportunities, while interviews identified strong student receptivity toward interactive digital learning. These findings establish specific design requirements for the proposed E-Module, including virtual laboratories, adaptive assessment, and personalized learning pathways targeting elevation to high competency levels (≥67%). This research contributes evidence-based foundations for technology-enhanced science education interventions addressing 21st-century competency development in resource-constrained contexts